PRODUCTION AND ECONOMIC RESULTS OF INTENSIVE CARP (Cyprinus Carpio) FARMING IN SERBIA - Rajić, Zoran; Vignjević-Đorđević, Nada; Čanak, Stevan (Economics of Agriculture, 2016)
Carp production in Serbia is traditionally conducted in large area fsh farms under a semiintensive farming system. Total area under fsh farms in Serbia amounts to approximately 11 thousand hectares, with 8.5 thousand hectares being under exploitation each year. In 2004, a signifcant intensifcation of production began at fsh farms in Serbia which have traditionally organized their production under a classic semi-intensive farming system. Intensifcation of production was undertaken with partial or complete feeding with pelleted complete feeds. That way carp production per area unit (kg/ha) was increased by over 50%. Apart from intensifcation by means of using the complete extruded feeds, construction of specialized fsh farms for intensive carp production started in 2003. At this moment (2016) their area amounts to several hundred hectares. Data from intensive carp fsh farms indicate that production of one- and two-year fsh has been approximately 3t/ha in the period from 2003 until today, with a mild increase during the last couple of years. With the purpose of determining the cost effectiveness of investments in fsh ponds for intensive carp production two organization-economic models have been analyzed in the study. The models have been formed based on in line with the specifc features of the Serbian carp farming, which has been analyzed both on the basis of data obtained from the scientifc and specialist literature but also from the production practice. Models of intensive carp production in technical and production sense have been defned in the study and production plans have been prepared. Therefore, based on such defned models, dynamic methods have been prepared for assessment of economic effects of the investments. The results of the analysis have demonstrated that investment in intensive carp production on 10ha fsh farm is not, and on 50ha fsh farm is barely economically justifable, as well as methods for improvement of economic effectiveness.